The Effect of Lavender Aromatherapy (Lavendula Angustifolia) on Anxiety Level in Labor at Kediri City Hospital - Affanin, Hanun; Kundarti, Finta Isti; Mediawati, Mika (Universitas Aisyiyah Yogyakarta, 2023)
Anxiety in mothers is a clinical problem that can cause maternal depression and affect development. However, there is actually no special treatment that can be given to maternity mothers to reduce the anxiety felt. Giving lavender aromatherapy is one way of reducing maternal anxiety before labor. This study aims to analyze the effect of lavender aromatherapy on the level of anxiety in labor. This quantitative research uses a quasi-experimental design and a pretest-posttest control design. The sampling for the research was carried out by using random sampling techniques. The sample was 60 maternity mothers in the active phase with 30 intervention group respondents and 30 control group respondents, with lavender aromatherapy intervention in one of the hospitals in Kediri. The results showed a difference in anxiety levels in the intervention group and the control group after lavender aromatherapy was given to maternity mothers. Lavender aromatherapy has been proven to affect the hypothalamus and reduce the secretion of corticotrophin-stimulating hormone through olfactory pathway stimulation, which can ultimately lower maternal anxiety levels before labor. The use of lavender aromatherapy in labor rooms in various services, both services at PUSKESMAS (Community Health Centre) and hospitals, should be considered to reduce maternal anxiety before delivery.